News Briefs. (Computer (00189162), 2013)
Topics include five suspects being charged in the US's largest financial hack, new cellular approaches on the verge of wider implementation, an MIT system that could make Internet communications faster, the possible upcoming release of long-awaited lithography equipment that could enable faster chips and extend Moore's law, smart streetlights, and a pen that recognizes misspelled words and alerts users while they write.